Implementation of Zabbix-Based Network Monitoring with Telegram and Web Reporting - Isnandar, Ahmad Yazid; Ridwandono, Doddy; Sembilu, Nambi (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
Effective network monitoring is essential in ensuring the stability and performance of campus IT infrastructure. This study aims to implement an open-source network monitoring system using Zabbix, integrated with Telegram alerts and a web-based visualization dashboard built with Laravel Filament. The development process follows the PPDIOO methodology, encompassing stages such as planning, installation, configuration, alert integration, and dashboard development. The system was implemented for the network infrastructure of two buildings at Universitas Pembangunan Nasional "Veteran" Jawa Timur: the Faculty of Computer Science Building (FIK2) and the Shared Lecture Building (GKB). The results show that the system effectively monitors the status of network devices, CPU and memory usage, DHCP leases, and network traffic. Additionally, it features real-time alerts via Telegram and web-based reports for visualizing network data. This solution enhances operational efficiency and offers a flexible and adaptive monitoring tool tailored to the needs of campus network management.